Athena: ESA's X‐ray observatory for the late 2020s. Issue 2 (21st March 2017) - Barcons, X.; Barret, D.; Decourchelle, A.; den Herder, J. W.; Fabian, A. C.; Matsumoto, H.; Lumb, D.; Nandra, K.; Piro, L.; Smith, R. K.; Willingale, R.
Abstract : Observations of the X‐ray sky after the next decade will most likely be dominated by Athena (Advanced Telescope for High ENergy Astrophysics), the second large mission of ESA's Cosmic Vision 2015–2035 programme. Athena has been conceived to address the "Hot and Energetic Universe" science theme, which focuses on the assembly and evolution of hot baryons in cosmic structures as well as the physics and energetic output generated by accreting super‐massive black holes, along with the relationship between the two processes, dubbed cosmic feedback. Thanks to its transformational capabilities, Athena will enable bringing all of today's XMM‐Newton's hot science topics to a new stage. In this paper, we summarize the Athena science case, science requirements, as well as the expected mission performance, mission concept, and its status.